Pokeweed Antiviral Protein Increases HIV-1 Particle Infectivity by Activating the Cellular Mitogen Activated Protein Kinase Pathway - Mansouri, Sheila; Kutky, Meherzad; Hudak, Katalin A. (PLOS ONE, 2012)
Pokeweed antiviral protein (PAP) is a plant-derived N-glycosidase that exhibits antiviral activity against several viruses. The enzyme removes purine bases from the messenger RNAs of the retroviruses Human immunodeficiency virus-1 and Human T-cell leukemia virus-1. This depurination reduces viral protein synthesis by stalling elongating ribosomes at nucleotides with a missing base. Here, we transiently expressed PAP in cells with a proviral clone of HIV-1 to examine the effect of the protein on virus production and quality. PAP reduced virus production by approximately 450-fold, as measured by p24 ELISA of media containing virions, which correlated with a substantial decline in virus protein synthesis in cells. However, particles released from PAP-expressing cells were approximately 7-fold more infectious, as determined by single-cycle infection of 1G5 cells and productive infection of MT2 cells. This increase in infectivity was not likely due to changes in the processing of HIV-1 polyproteins, RNA packaging efficiency or maturation of virus. Rather, expression of PAP activated the ERK1/2 MAPK pathway to a limited extent, resulting in increased phosphorylation of viral p17 matrix protein. The increase in infectivity of HIV-1 particles produced from PAP-expressing cells was compensated by the reduction in virus number; that is, virus production decreased upon de novo infection of cells over time. However, our findings emphasize the importance of investigating the influence of heterologous protein expression upon host cells when assessing their potential for antiviral applications.